The Role of Mucins in Cancer and Cancer Progression: A Comprehensive Review - Clare Chen; Ameena Patel; Lusine Demirkhanyan; Christopher S. Gondi (Current Issues in Molecular Biology)
Mucin, a heavily glycosylated glycoprotein, serves an important function in forming protective and immune defense barriers against the exterior environment on epithelial surfaces. While secreted-type mucins are involved in mucous production, transmembrane mucins, which contain O-glycosylated tandem repeats, play a pivotal role in cellular signaling, especially in immune modulation and mediating inflammatory response. However, dysregulation in mucin expressions, such as MUC1, MUC2, MUC4, MUC5AC, and MUC16, have been observed in many cancer cells. More specifically, alterations in the expression and glycosylation of MUC1 have been associated with the upregulation of pathways involving the cell proliferation, angiogenesis, migration, and invasion of cancer cells. With mucin’s extensive involvement in cancer biology, several mucin biomarkers, such as CA125, CA19-9, and CEA, have been utilized as diagnostic and prognostic monitoring biomarkers in ovarian, pancreatic, and colon cancer. Vaccines and antibody therapy against abnormal mucin glycosylation have also been investigated for potential therapy for mucin-related cancers that are resistant to traditional chemotherapy agents. Despite the lack of specificity in mucin biomarkers and challenges in efficient drug delivery systems, the current advancement in mucin-targeted immunotherapy highlighted the pivotal potential in developing therapeutic targets to improve cancer prognosis.